A class of symmetric balanced incomplete block designs with autocorrelated errors - Raghavarao, Damaraju; Shu, Xiaohua (Utilitas Mathematica, 2011)
In this paper we will rearrange the treatments in each block of a symmetric balanced incomplete block design with λ = I and use it under autocorrelation error structure of the plots in a block. The C-matrix of estimated treatment effect under autocorrelation is given and its relative efficiency compared to the symmetric balanced incomplete block designs with independent errors is provided.